THE ROLE OF MYTH IN ESCALATING THE CONFLICT BETWEEN ISRAEL-PALESTINE - Abdul Mujib (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2019)
Myth as the basic of information before conducting life in society can escalate the sight toward other perspective,and make conflicting between Israel-Palestine. They are defending their myth. The myth of David and Goliathwhich stone as a tool in conquering the monster Goliath, it is been trying for youth Palestinian to beat Israel.Whereas, according to Abu Nimer, the reason for Palestinian using stone is like symbol that they want to shownon-violent. However, by using stone, Israel fears that the story of David and Goliath will happen to them, yetthe story is opposite. Now, the Israel becomes Goliath, and youth Palestinian becomes David who is throwingstone to the monster. By using Kepferer’s theory about power of myth, this article wants to analyze how strongthe power of myth in the conflict of Israel-Palestine on the perspective of throwing stones.